Analisis Kesulitan Linguistik dalam Pemahaman Istilah Matematika Berbahasa Inggris oleh Mahasiswa Teknik Informatika - Andi Nuzul Hikmah Buana; Misveria Villa Waru; Riski Aditia (EQUALS: Jurnal Ilmiah Pendidikan Matematika, 2025)
This study explores the linguistic challenges experienced by Informatics Engineering students in understanding English mathematical terminology used in academic discourse. As English remains the dominant language in science and technology, the ability to comprehend subject-specific vocabulary is crucial for non-native learners. The research aims to describe the types of linguistic difficulties students encounter, identify contributing factors, and propose effective instructional strategies. Using a descriptive qualitative design supported by quantitative data, the study involved 60 students who had completed courses in basic mathematics, linear algebra, and algorithms. Data were obtained through mathematical vocabulary tests, questionnaires, semi-structured interviews, and document analysis. The results show that students face notable difficulties with polysemous and homonymous words, syntactic complexity in mathematical texts, and limited translation skills. Although students easily recognize technical terms such as derivative and matrix, they often misinterpret contextual words like root or function due to multiple meanings. The findings indicate that linguistic competence directly influences the comprehension of mathematical concepts. The novelty of this study lies in integrating linguistic and disciplinary perspectives through an ESP/EAP-based approach. It also recommends adaptive and technology-assisted pedagogy to strengthen students’ academic literacy and understanding of English mathematical terminology.